Contemporary global media circulation based on fan translation: A particular case of Thai fansubbing. (December 2019) - Wongseree, Thandao; O'Hagan, Minako; Sasamoto, Ryoko
Abstract: This article argues that fan translation serves as a contemporary, alternative mechanism for the circulation of global media texts. By focusing on the fan subtitling practice in the case of Thai fansubbing of a Korean TV programme, we observe unique ways in which fans exploit semiotic resources to produce fansubs in relation to professional subtitling norms. For example, novel features of fansubs include the treatment of "impact captions" prevalent on Korean TV which are typically untranslated in official Thai translations as these captions are not common in Thailand. Using Actor Network Theory (ANT) as a framework, we analyse survey and interview data collected from Thai fansubbing communities of the Korean TV show Running Man (Wongseree, 2018). The data indicate the close interrelationship which seems to develop between fansubbers and "non-translating" members of fan communities. The previously less recognised importance of such an inter-dependency points to the building of trust, especially epistemic trust, which underlies fansubbing practices. We thus argue that this modern alternative circulation mechanism for global media texts can be characterised by the particular way fans exploit semiotic resources and the way in which it is supported by epistemic trust within the fan community.